APPROACHES TO CHORIONIC GONADOTROPIN QUANTITATIVE DETERMINATION IN ANTI-DOPING CONTROL - I. O. Zvereva; N. B. Savelieva; P. V. Postnikov; Yu. A. Efimova; M. A. Dikunets (Тонкие химические технологии, 2017)
The article presents the results of the first stage of development of a new quantitative method for human chorionic gonadotropin (hCG) determination by means of ultra-high performance liquid chromatography coupled to tandem mass spectrometry (UPLC-MS/MS) to uncover doping abuse by athletes. The identified tryptic peptides correspond to the most abundant hCG isoforms: the α- and β-subunits, the nicked and β-core fragment of the hormone. Identification and sequencing of specific fragments were performed with the use of nanoLC-MS/MS. A high resolution / high accuracy hybrid mass-spectrometer was applied. Optimization of mass-spectrometric determination of selected specific peptides was accomplished by UPLC-MS/MS. Quantitative evaluation of hCG using specific fragments determination by UPLC-MS/MS allows to detect corresponding hCG isoforms. This significantly increases the method specificity and decreases the probability of false-positive results.